2021
DOI: 10.1515/jbcpp-2020-0533
|View full text |Cite
|
Sign up to set email alerts
|

Increase in SARS-CoV-2 infected biomedical waste among low middle-income countries: environmental sustainability and impact with health implications

Abstract: Studies have shown that severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) is a highly infectious disease, with global deaths rising to about 360,438 as of 28 May 2020. Different countries have used various approaches such as lockdown, social distancing, maintenance of personal hygiene, and increased establishment of testing and isolation centers to manage the pandemic. Poor biomedical waste (BMW) management, treatment, and disposal techniques, especially SARS-CoV-2 infected BMW, may threaten the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…Unlike developed countries, developing countries face more challenges in implementing waste management systems owing to technical and economic constraints ( Ferronato and Torretta, 2019 ). Furthermore, without proper waste treatment, coronavirus disease (COVID-19) infected wastes containing viable viruses and infectious pathogens could be a source of outbreak and pandemic ( Olaniyan et al, 2022 ). Antimicrobial resistance (AMR) represents a global threat where microbial pathogens continue to evolve and develop resistance to existing antibiotics, putting the world in another pandemic ( Aljeldah, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike developed countries, developing countries face more challenges in implementing waste management systems owing to technical and economic constraints ( Ferronato and Torretta, 2019 ). Furthermore, without proper waste treatment, coronavirus disease (COVID-19) infected wastes containing viable viruses and infectious pathogens could be a source of outbreak and pandemic ( Olaniyan et al, 2022 ). Antimicrobial resistance (AMR) represents a global threat where microbial pathogens continue to evolve and develop resistance to existing antibiotics, putting the world in another pandemic ( Aljeldah, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research by Rahul Rajak et al, 2021 has shown that India's MW by the COVID-19 pandemic has reached 32,996 tons in only the last 6 months of 2020 [ 29 ]. The study by Olugbemi T Olaniyan et al pointed to the rapid increase in PPE and other biomedical wastes by the COVID-19 pandemic [ 30 ]. At the same time, this study also shows that the loopholes in the medical waste management plan can have serious consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the dumping of recyclables causes soil pollution. Olaniyan et al ( 2021 ), Subramanian et al ( 2021 ) …”
Section: Factors Hindering 3pl In Bmw Managementmentioning
confidence: 99%
“…Nevertheless, there is no such effort for recycling among healthcare centers as well as in 3PL disposal factories (Sharma et al 2021 ). Many 3PL disposal factories dump these wastes in the soil which causes soil pollution as well as the release of different pollutants into the environment (Olaniyan et al 2021 ). In addition, due to fewer traits of recycling, treatment and disposal expense of 3PL increases.…”
Section: Factors Hindering 3pl In Bmw Managementmentioning
confidence: 99%